A Multilevel Approach for Reducing Mental Health and Substance Use Disparities Affecting Bisexual Individuals. Issue 2 (May 2019) - Feinstein, Brian A.; Dyar, Christina; Pachankis, John E.
Abstract: Despite bisexual individuals being at increased risk for mental health and substance use problems, clinicians' ability to provide affirmative and competent care to bisexual clients is limited by their lack of bisexual-specific training. To address this common gap in training, this article provides a brief review of bisexual health disparities and the factors that influence them. Then, we describe a multi-level approach for improving the health and well-being of bisexual individuals. This approach addresses factors that influence health at the micro-level (e.g., strategies that clinicians can use to help bisexual clients cope with stigma-related stressors), mezzo-level (e.g., adaptations to clinical environments and training programs that promote bisexual-affirmative care), and macro-level (e.g., advocating for political change and implementing strategies to reduce prejudice against bisexual individuals at the population-level). Specifically, we describe how clinicians can adapt evidence-based interventions to tailor them to the needs of their bisexual clients. Additionally, we discuss the need for bisexual-affirmative clinical training and provide recommendations for how clinical training can be adapted to prepare clinicians to work effectively with bisexual clients. Finally, we describe how population-level interventions can be used to reduce prejudice against bisexual individuals in order to reduce bisexual health disparities. Given the striking health disparities affecting bisexual individuals, there is a critical need to develop, test, and disseminate interventions to improve the health of this population and to prepare clinicians to provide bisexual-affirmative care. Highlights: Bisexuals are at increased risk for mental health problems compared to monosexuals. Many clinicians lack training in providing bisexual-affirmative care. A multi-level approach for reducing bisexual health disparities is proposed. Clinicians can tailor evidence-based interventions to bisexual clients' needs. Population-level interventions can be used to reduce bisexual stigma at its source.